Mathematics Learning Research for Deaf Elementary School Students in Indonesia: A Systematic Literature Review - Alifulloh, Wenda; Juandi, Dadang; Ismail, Mochamad Tubagus; Khoirunnisa, Azizah Nurul; Nuralam, Humam (Universitas Pendidikan Indonesia, 2024)
Mathematics education for deaf elementary school students is a crucial goal outlined in Article 31 of Indonesia's 1945 Constitution. Immediate and focused interventions are essential to support their mathematical education, a fundamental field for problem-solving in various aspects of life. This study involves a systematic literature review (SLR), examining the substance of multiple scholarly articles listed on Google Scholar and published across Indonesia from 2013 to 2022. Its primary focus is on different facets concerning the learning of mathematics for elementary school students who are deaf in Indonesia. While there hasn't been a notable upward trend in research studies focused on the learning of mathematics among deaf elementary school students over the past three years, it is revealed that the predominant research design is quantitative. The most researched material is